Intentions and Childbearing in a Cross-Domain Life Course Approach: The Case of Australia - Maria Rita Testa; Danilo Bolano (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2019)
In Australia and other affluent societies people tend to report a number of desired children which is clearly higher than the number of children they eventually bear. In the effort to explain such an inconsistency, demographers have studied the correlates of the link between pregnancy intentions and births. Drawing on data from the "Household Income and Labour Dynamics in Australia" (HILDA) survey, we situate, for the first time, intentions and events in a unified and multidimensional life course framework. We examine the intention-outcome fertility link across a plurality of life course domains and in a genuine couple approach. Education, work, and residence are selected as domains closely related to the family formation process. Results show that pregnancy intentions are often part of a multidimensional life course plan and that the cross-domain effects are gendered and parity specific. Moreover, cross-domain events have stronger influence than cross-domain intentions. A change of residence is directly correlated with a childbirth if it is the outcome of a previous plan and the couple has already made the transition to parenthood. Resumption of studies is inversely correlated with the birth of a child irrespective of whether the event was planned or not by either one of the partners. Finally, a change of job decreases the chance of having a first child but only if experienced by the female partner while it decreases the chance of an additional child only if previously planned or experienced by both partners. Such results confirm the relevance of work-family conflict as one of the drivers of low fertility and outline the usefulness of a holistic life course approach in the analysis of reproductive decision-making.
Keywords: 300; Intentions; fertility; life course; family formation; Australia; couple-level analysis